HUBUNGAN PERAN PEMBIMBING KLINIK DENGAN METODE PROBLEM BASED LEARNING PADA MAHASISWA KEBIDANAN DI RSUD CIBINONG - Dina Martha Fitri; Nurhidayah Nurhidayah (Universitas Indraprasta PGRI, 2020)
PBL or problem based learning is a learning approach that uses real-world problems as a context for students to learn about critical thinking and problem-solving skills for which a clinical counselor is needed. So the purpose of research to find out